Badminton Court Agility Test - Nanang Kusnadi; Dicky Tri Juniar; Ucu Muhammad Afif (STKIP Muhammadiyah Kuningan, 2022)
In 2016 PP PBSI published a book of criteria and physical parameters for athletes entering national training and version 1 for athletes. There is an agility test called the agility court. However, this agility court test does not yet have the validity and reliability values ​​needed for a trial, so it still needs to be tested for validity and reliability. This study aims to reveal the truth and reliability of the badminton game agility court test in athletes aged from children to Adolescents. This research uses a descriptive method. The population used in this study were all badminton athletes in the Tasikmalaya region, and as many as 103 people were sampled in this study by purposive sampling. Analysis of the data used is to test the level of validity and reliability of the test using Product Moment correlation through IBM SPSS 26. The study results for athletes from the City of Tasikmalaya have a validity degree of 0.772, including the High variety and a reliability degree of 0.921, including the High variety. Athletes in Tasikmalaya Regency have a validity degree of 0.767, including the High variety and a reliability degree of 0.939, including the High variety. The conclusion is that the badminton agility court test is valid and reliable, and this test can be used to measure the agility of athletes from children to Adolescents.